Improving the precision of micro-EDM for blind holes in titanium alloy by fixed reference axial compensation - Lin Chaohui (De Gruyter, 2021)
During the electrical discharge machining (EDM) process, the tool electrode wear is inevitable, which affects the process precision of the micro-hole. In the present experimental investigation, a fixed reference axial compensation (FRAC) method is proposed to enhance the machining precision of micro-hole. The effect of pulse power, compensation methods, and electrode materials on the depth and roundness factor of micro-hole are explored. The experiment results show that the FRAC method can realize the accurate compensation and reach the expected depth hole processing. When the FRAC is used, the depth deviation is less than 0.43%, and the minimum difference from the expected depth is only 0.106 µm. In addition, the micro-holes of tungsten steel and brass electrodes machine by the FRAC method were close to the expected depth, the difference from the expected depth less than 0.7%, but the bottom of micro-hole produced a cone. However, compared to tungsten steel and brass electrodes, the copper electrode has a better processing performance, the roundness factor is up to 79.8%. When the long-pulse power supply is applied, the expected depth of 400–1,600 µm blind holes with a better processing shape, and the phenomenon of the cone at the bottom are not apparent. Therefore, the proposed FRAC method can be utilized in many high-end manufacturing fields to improve the precision of the micro-hole for micro features.